Collision tumors in the gastrointestinal tract: a rare case series - Bhattacharya A; Saha R; Biswas J; Biswas J; Ghosh B (International Medical Case Reports Journal, 2012)
Aruna Bhattacharya,1 Rama Saha,1 Jayanta Biswas,2 Jhuma Biswas,1 Biswajit Ghosh11Institute of Postgraduate Medical Education and Research, 2NRS Medical College and Hospital, Kolkata, West Bengal, IndiaAbstract: A collision tumor is one where histology shows the presence of two distinct primaries involving the same organ without intermixture of individual cell types, ie, a side by side pattern. Here we present three rare cases of collision tumors involving the stomach and transverse colon. There were two cases of collision tumors involving the stomach, one of which was a combination of adenocarcinoma and low-grade non-Hodgkin's (mucosa-associated lymphoid tissue) lymphoma, and the other showed the presence of non-Hodgkin's lymphoma involving the entire stomach wall along with adenocarcinoma infiltrating the muscle layer. The third case comprised a mucinous adenocarcinoma and carcinoid tumor in the large gut.Keywords: collision tumor, histology, gastrointestinal tract